The Relationship Of Hypertension With Increased Intraocular Pressure In Glaucoma Patients In Polyclinics Ambon Vlissingen Eye - Laisina, Christofer B. (Enrichment: Journal of Multidisciplinary Research and Development, 2023)
Glaucoma is a progressive optic neuropathy that characterized by optical nerve damage and loss function were of visual field. This is the second leading cause of blindness worldwide. statistic showed 0.5% of Indonesian people suffering from glaucoma and one of the factors that cause glaucoma is hypertension. The purpose of this study was to determine the correlation of hypertension with increased intraocular pressure in glaucoma patients at Ambon Vlissingen Eye Polyclinic, on January of 2018 using analytical descriptive with cross sectional approach. The number of samples were 38 respondents. Data collection was done through observation sheet and interview guide. Data were analyzed by using chi square test. This study shows the value of p = 0.000 <? = 0.05 which means that there was a relationship between hypertension with an increasing in intraocular pressure in Ambon Vlissingen Eye Polyclinic. conclusion there was a relationship between hypertension with increased intraocular pressure on Eye Polyclinic Ambon Vlisingen. It is expected that health officer of Eye Polyclinic Ambon Vlisingen in order to improve the quality of service so that morbidity and mortality due to glaucoma and hypertension can be reduced.